Pengaruh Terpaan Pesan Host Live Streaming terhadap Keputusan Pembelian Produk: Studi Kuantitatif tentang Pengaruh Terpaan Pesan Host Live Streaming Rahsa Nusantara terhadap Keputusan Pembelian Produk Anggota Komunitas Rumah Tumbuh Bersama - Dara Natasya Putri; Kismiyati El Karimah; Agus Setiaman (Institut Nalanda, 2025)
This research is titled “The Influence of Host Live Streaming Message Exposure on Product Purchase Decisions (A Quantitative Study on the Influence of Host Live Streaming Messages from Rahsa Nusantara on the Purchase Decisions of Members of the Rumah Tumbuh Bersama Community). This study aims to determine the significance of the influence of persuasive messages from the Rahsa Nusantara live streaming host on purchase decisions. The method used in this research for data analysis is multiple linear regression. The number of respondents in this study is 28 individuals selected through probability sampling techniques. Data collection was conducted by distributing questionnaires to members of the Rumah Tumbuh Bersama Community. The results of the study indicate that message exposure, which include message content, message structure, and message format, have a positive influence on purchase decisions. However, the dimensions of the sub-variables of message structure and message format do not significantly affect purchase intention. The largest sub-variable influencing purchase decisions is the message content sub-variable.